The Perceptions of English Education Students Towards the Use of Code-mixing in English and Teaching Learning Process at UIN Sayyid Ali Rahmatullah Tulungagung - Zubaedah, Zubaedah; Chojimah, Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to find out the perceptions of English education students in the sixth semester toward the use of code-mixing in the main activity of the teaching and learning process at UIN Sayyid Ali Rahmatullah Tulungagung. The research design is a survey with a quantitative approach. The data were obtained from 26 English students in the sixth semester that had filled out a link questionnaire that had been distributed. Based on findings obtained from the questionnaire, revealed that 77% of students have a positive perception, they also agreed that the use of code-mixing has a positive impact on them; it can be used to make fun and lively learning in the classroom and easy to understand the lesson. 19% of students have a neutral perception of the impact of code-mixing. Then, 4% of students who have a negative perception think that code-mixing does not positively impact them, and they feel uncomfortable when using code-mixing in the English teaching and learning process.